Proceedings of the 26th International Conference on World Wide Web 2017
DOI: 10.1145/3038912.3052613
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Link Successful on Wikipedia?

Abstract: While a plethora of hypertext links exist on the Web, only a small amount of them are regularly clicked. Starting from this observation, we set out to study large-scale click data from Wikipedia in order to understand what makes a link successful. We systematically analyze effects of link properties on the popularity of links. By utilizing mixed-effects hurdle models supplemented with descriptive insights, we find evidence of user preference towards links leading to the periphery of the network, towards links … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…This hints to the fact that -to some extent -users enter Wikipedia by search on more central articles, and then navigate outwards from more to less central nodes. This is consistent with previous findings studying navigation on Wikipedia [7]. Regarding articles with different topical alignments, we see certain evidence that the thematic domain of a user's information pursuit seems connected with the "mode" of how this information is attained.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This hints to the fact that -to some extent -users enter Wikipedia by search on more central articles, and then navigate outwards from more to less central nodes. This is consistent with previous findings studying navigation on Wikipedia [7]. Regarding articles with different topical alignments, we see certain evidence that the thematic domain of a user's information pursuit seems connected with the "mode" of how this information is attained.…”
Section: Discussionsupporting
confidence: 92%
“…Dimitrov et al conducted a large-scale study on the navigational behavior on Wikipedia. They found that users tend to select links located in the beginning of Wikipedia articles and links leading to articles located in the network periphery [6,7]. By constructing a navigational phase space from transition data, Gilderslave and Yasseri studied internal navigation on Wikipedia and identified articles with extreme, atypical, and mimetic behavior [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamprecht et al investigate how different naïve link selection models compare to data from the Wikipedia clickstream, finding that a model based on article structure best explains user navigation choices [23]. This work is built on by Dimitrov et al, by using a more complex model utilizing Bayesian inference, supplemented by mixed effects hurdle models using network, semantic and visual features to predict transition counts in clickstream data [24]. Finally, 'Why We Read Wikipedia' [25] provides a comprehensive overview of navigation on Wikipedia to create a taxonomy of users, their behaviours and their motivations by matching survey responses with data including user clickstreams.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, I study the relationship between the link properties and the link popularity as measured by transitional click data. To that end, I formulate navigational hypotheses based on different link features, i.e., network features, semantic features and visual features [2,3]. The plausibility of these hypotheses is then tested using a Markov chain-based Bayesian hypothesis testing framework.…”
mentioning
confidence: 99%